A Rare Case of Extramedullary Plasmacytosis - Kristen L. Farraj DO; Aboud Kaliounji MS-IV; Deepthi Kagolanu MD; Nausheer Khan MD (SAGE Publishing, 2021)
Plasmacytosis is the abnormal proliferation of plasma cells in tissue, bone, blood, or exudates. Mucous membrane plasmacytosis is a rare form of plasmacytosis that is usually idiopathic in nature. A 68-year-old female underwent a diagnostic and therapeutic esophagogastroduodenoscopy, which revealed a friable antral erythematous gastric fold and a gastric polyp. Subsequent pathological testing was positive for diffuse polyclonal plasma cell proliferation, which was suggestive of a gastric plasmacytosis. In this article, we report a rare presentation of mucous membrane plasmacytosis.